Firms, jobs, and gender disparities in top incomes: Evidence from Brazil - Felipe Benguria (W.E. Upjohn Institute for Employment Research, 2020)
This paper studies the gender disparities among top incomes in Brazil during the period 1994-2013 using administrative data on the universe of formal-sector job spells and detailed information on educational attainment, employers, and occupations performed. Over these two decades, differences in pay and participation between genders have narrowed, yet the process has been slow and women are still severely underrepresented, especially within the very top percentiles of the earnings distribution. The following findings highlight the role of firms and occupations in explaining these patterns. At the start of the period, women in the top percentile of the distribution owe a larger fraction of their earnings to working at high-paying firms than do men, while men's top incomes are in excess of their firms' average pay. In addition, belonging to the top percentile is initially much more persistent for men than for women. Both of these differences have vanished over time. I also document that the increase in the share in participation of women in top percentiles is primarily a within-firm and within-occupation phenomenon, which suggests that the evolution of cultural and institutional elements deserves further examination. Finally, I study the careers of female and male top earners, finding that the path to the top percentiles of the distribution is quite different across genders: Top-earning women work in larger firms from the start of their careers. Top-earning men earn large earnings premia above what their firm average pays throughout their career, and after their mid-30s switch employers at a higher frequency than women.
Keywords: E24; G10; J31; 330; Top earners; Glass ceiling; Gender wage gap